Aging Properties and Mechanism of Microwave-Activated Crumb Rubber Modified Asphalt Binder - Zhou, Tao; Zhou, Jianing; Li, Qidong; Li, Bo (Frontiers in Materials, 2020)
Although crumb rubber modified asphalt (CRMA) has a better performance than matrix asphalt (MA) in road engineering, the application bottlenecks of this material lies in its high viscosity, poor workability and bad storage stability. Microwave technology is one of the solutions to the above problems. The objective of this study was to investigate the physical and chemical changes before and after aging of CRMA which was prepared by microwave activated crumb rubber, and the aging mechanism of microwave-activated crumb rubber modified asphalt (MACRMA). Through penetration, softening point, ductility, viscosity and DSR test, the high and low temperature performance and temperature sensitivity of MA, CRMA and MACRMA before and after aging were studied. These tests results revealed that microwave treatment can improve the anti-rutting ability and the anti-aging performance of rubber asphalt. According to gel permeation chromatography (GPC) test, the distribution changes of the internal molecular content of the three asphalts were determined during the aging process. Its test results showed that aging effect accelerated the conversion of small molecules to large molecules in asphalt, and the value of large molecular size (LMS) increases more after long-term aging. The microwave activation made the swelling reaction more intense, thereby delayed the conversion of LMS in the rubber asphalt. In addition, LMS has a high correlation with test indicators. The fourier transform infrared spectroscopy (FTIR) test was used to measure the functional group changes of each asphalt. The FTIR spectra indicated that microwave activation is mainly a process of physical change. The carbonyl and sulfoxide functional group indices of MACRMA were lower than those of MA and CRMA, which also confirmed that MACRMA has a better anti-aging ability.